Kajian Pendapatan Nelayan di Kabupaten Bantul Dengan Pendekatan Sustainable Livelihood - Lina Lathifah; Rifki Khoirudin (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
This study aims to determine and analyze the factors that affect the income of gill net fishermen in Bantul Regency, especially in the villages of Poncosari, Gadingsari, Srigading, and Parangtritis with a sustainable livelihood approach. The data used in this study are primary and secondary data. The analytical tool used is multiple linear analysis (Ordinary Least Square). The sample in this study amounted to 122 respondents who were selected using a simple random sampling method (Simple Random Sampling). The dependent variable used in this analysis is the income of fishermen and the independent variables are human capital as measured by labor, age and experience of fishermen, natural capital as measured by distance traveled, financial capital as measured by working capital, physical capital as measured with ownership of boats and means of production, and social capital that can be measured from participation in organizations. Based on the analysis carried out, it was found that labor and working capital had a significant effect on the income of gill net fishermen in Bantul Regency, while age, experience, mileage, ownership of boats and production equipment, and organizational participation were not significant on the income of gill net fishermen in Bantul Regency.